1499. Incidence of Community Acquired Pneumonia by Age and Comorbid Conditions in the Veterans Health Administration (VHA). (31st December 2020) - Bej, Taissa A; Song, Sunah; Wilson, Brigid; Banks, Richard; Briggs, Janet; Jump, Robin; Perez, Federico
Abstract: Background: Community acquired pneumonia (CAP) remains a major cause of morbidity and mortality. Risk factors for CAP are often grouped as moderate- (e.g., diabetes mellitus, chronic liver, lung, or heart disease) and high-risk (e.g., immunosuppressive) conditions, which in turn influences preventative strategies, notably pneumococcal vaccination. Here, we use the national VHA databases to assess the risk of CAP among adults, expanding on previous work by using administrative data to assess the incidence of CAP among people with > 1 moderate risk condition Methods: We used the national VHA databases merged with claims summaries from the Centers for Medicare and Medicaid Services (CMS) to identify patients receiving clinical care in the VHA without clinical Medicare claims in 2016-2017. Within this population, we identified CAP cases defined by the presence of a diagnostic code for pneumonia, chest X-ray, and antibiotics as well as the absence of healthcare exposure or antibiotics in prior 90 days. We determined the total patient years at risk and calculated incidence rates by age group and by moderate- and high-risk comorbid conditions. Results: We identified 37, 348 CAP cases in 7.9 million person-years at risk and observed similar annual rates in 2016 and 2017 (468.9 and 472.2 cases/100, 000 person-years, respectively). The prevalence of high-risk conditions and incidence of CAP increased with age whereas the prevalence of >1 moderate-risk condition peaked for ages 50-64 and 65-74 years (Table ). The incidence of CAP among those with > 1 moderate-risk condition exceeded that of patients with high-risk conditions across all age strata (Figure ). Table Figure Conclusion: Age-adjusted analysis revealed that the greatest burden of CAP occurs in patients with > 1 moderate-risk condition, even compared to those with a high-risk condition. Our analysis of CAP based on national VHA data suggest that additional preventative health measures directed at individuals older than 50 years with > 1 moderate-risk condition may help to reduce the burden of CAP and limit its morbidity and mortality. Disclosures: Robin Jump, MD, PhD, Accelerate (Grant/Research Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support, Advisor or Review Panel member)Roche (Advisor or Review Panel member) Federico Perez, MD, MS, Accelerate (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)